1984
DOI: 10.7326/0003-4819-100-4-535
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-Associated Thrombocytopenia

Abstract: Heparin-associated thrombocytopenia is a relatively common complication of heparin therapy occurring in approximately 5% of the patients who receive this drug. The incidence is higher with bovine heparin then with porcine heparin. Onset of heparin-associated thrombocytopenia usually occurs 6 to 12 days after initiation of treatment and by itself has a low morbidity. Heparin-associated thrombocytopenia plus arterial thrombosis can cause major complications including stroke, heart attack, and death. The incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
144
0
20

Year Published

1985
1985
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(168 citation statements)
references
References 42 publications
4
144
0
20
Order By: Relevance
“…Stored serum collected from Cases 2 and 3 immediately before they began therapeutic doses of heparin revealed that these antibodies were already present, the result of exposure to heparin flushes during the previous 3 weeks. This presensitization was consistent with the immediate fall in platelet count following initiation of the higher dose of heparin in Case 2 [19].…”
Section: A S E R E P O R T : H E P a R I N F L U S H E S A N D H I Tsupporting
confidence: 75%
“…Stored serum collected from Cases 2 and 3 immediately before they began therapeutic doses of heparin revealed that these antibodies were already present, the result of exposure to heparin flushes during the previous 3 weeks. This presensitization was consistent with the immediate fall in platelet count following initiation of the higher dose of heparin in Case 2 [19].…”
Section: A S E R E P O R T : H E P a R I N F L U S H E S A N D H I Tsupporting
confidence: 75%
“…Therefore, the circulatory and excretory system of animals exposed to the medicinal plant may be adversely affected. Certain medicinal herbal preparations or convectional drugs or chemicals adversely affect various blood components [15,8]. Decrease or increase in cell counts and depletion of plasma constituents or their elevation beyond reference range could equally demonstrate haematoxicity [5].…”
Section: Discussionmentioning
confidence: 99%
“…To 140 µL of pre-warmed donor PRP, 220 µL of patient's heatinactivated PPP was added to a cuvette containing a stir bar, which was placed in the aggregometer (ChronoLog, Havertown, PA). To this, 40 µL of 2.5 U mL 1 of UFH was added (final UFH concentration = 0.25 U mL 1 ) and the aggregation response was monitored for up to 5 min. The test was considered positive for HIT, if there was >20% platelet aggregation response due to HPF4 antibodies as per the assay criteria.…”
Section: Heparin-induced Platelet Aggregation (Hipa)mentioning
confidence: 99%
“…Heparin induced thrombocytopenia (HIT) is emerging as an important complication not only of unfractionated heparins (UFH), but also of low molecular weight heparins (LMWH) which are widely used as antithrombotic agent for both therapeutic as well as surgical indications [1] . Ethnic variation in prevalence of HIT is known to exist [2] .…”
Section: Introductionmentioning
confidence: 99%